Enhancing Civic Education and University Quality Management: An Innovative Approach - Nazira , Diusheeva; Kylych , Kadyrkulov (Journal of Ecohumanism, 2025)
In modern socio-economic conditions, the problem of civic education of the population of the country acquires special significance. The multifaceted nature of this problem requires different approaches to its consideration and is associated both with increasing requirements for the formation of a person - a citizen, for the process of civic education, for the civic qualities of an individual, and with a change in value guidelines, when universal human values and the legal culture of people become priorities. Studying the problem of civic education at different stages of its evolution allows us to critically comprehend the process of its formation and development and use the most advanced ideas and experience for the further development of this problem. A historiographic review of scientific and pedagogical literature on the topic indicates that researchers of the problems of civic education have most fully studied the issues of civic education and the formation of a citizen, various aspects of its organization in the educational process of a comprehensive school. The article deals with the problems of the didactic system of improving the quality management of higher education by means of IT technologies from the point of view of the process approach. Innovative technologies make it possible to increase the efficiency of the university's quality management system by optimizing the structure of all main and auxiliary processes. The article is devoted to the problems of implementing automation of the process of assessing the quality of the educational process, the quality of teaching individual disciplines at the university, the creation of an effective management system based on the principles of quality management. Special attention was paid to the management structures of the higher education system of Kazakhstan, where information systems based on computer technologies are used. Specified for the purpose of implementation as well as operation Attention is drawn to the contradiction between the requirements of the international standard ISO 9000 series, which regulate the conduct and study of the opinions of consumers of educational services in the monitoring mode, and the lack of a properly developed information system that allows collecting, processing and presenting information about customer satisfaction